2019
DOI: 10.1111/sjop.12591
|View full text |Cite
|
Sign up to set email alerts
|

Reading thousands of books and traveling thousands of miles: Diversity of life experience mediates the relationship between family SES and creativity

Abstract: This study examined the relationship between family SES and children’s creativity, and tested the mediating role of diversity of life experience in this relationship. A total of 204 undergraduates (54 males and 150 females), aged between 17 and 23 years, completed a family SES questionnaire, diversity of life experience questionnaire, biographical inventory of creative behaviors, and alternative uses tasks (AUT). The results showed positive associations between family SES, diversity of life experience, and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…However, the opportunity to work in this type of occupation is not equally distributed across social strata: those with lower socioeconomic backgrounds are less likely to have intrinsic motivation for an occupation [25]. Utilizing community resources is suggested to reduce the gap related to socioeconomic strata [16]. Our study showed that the benefit of public libraries was more prominent among adolescents with the lowest income category.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the opportunity to work in this type of occupation is not equally distributed across social strata: those with lower socioeconomic backgrounds are less likely to have intrinsic motivation for an occupation [25]. Utilizing community resources is suggested to reduce the gap related to socioeconomic strata [16]. Our study showed that the benefit of public libraries was more prominent among adolescents with the lowest income category.…”
Section: Discussionmentioning
confidence: 71%
“…Xu and Pan reported that differences in life experience mediate the association between high socioeconomic status and creativity among university students. They suggested that this gap could be reduced by utilizing shared resources [16]. Further, social events held at public libraries can provide opportunities for children to be exposed to different experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies (Shi et al ., 2013; Xu & Pang, 2020), family SES was measured by five indicators: paternal occupation, maternal occupation, paternal education, maternal education, and family monthly income. Parental occupation comprised five categories: (1) the unemployed, temporary workers, unskilled workers, and farmers; (2) manual workers, construction workers, and lower level technicians; (3) white‐collar workers and middle level technicians; (4) middle‐class managers and civil servants; (5) senior executives, senior technicians, and leaders of government agencies.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, family monthly income was classified into 10 levels (RMB): (1) less than 2,000; (2) 2,000–3,000; (3) 3,000–4,000; (4) 4,000–5,000; (5) 5,000–6,000; (6) 6,000–7,000; (7) 7,000–8,000; (8) 8,000–9,000; (9) 9,000–10000; (10) more than 10,000. Prior studies have validated the appropriateness of using these items to measure family SES (Shi et al ., 2013; Xu & Pang, 2020). In the current study, the internal consistency of this measurement, as indicated by McDonald’s Omega (McDonald, 1999), was satisfactory (0.82).…”
Section: Methodsmentioning
confidence: 99%
“…For example, people who grew up in disadvantaged families tended to have less stimulating home environments, insufficient parental involvement, and experienced maladaptation at school, resulting in inadequate personal development ( Rothe et al 2014 ; Seabra-Santos et al 2021 ; Skopek et al 2017 ). Due to inadequate development, the creative performance of people in disadvantaged situations cannot be compared with people in advantageous situations ( Xu and Pang 2020 ). Runco ( 1993 ) proposed that creative potential is widely distributed to both disadvantaged groups and advantaged groups and that the low creative performance of disadvantaged groups is related to them having more undiscovered creative potential.…”
Section: Introductionmentioning
confidence: 99%